Identifying non-functional requirements for a CRM system - Rudenko, М. О.; Sotnik, S. V. (ONUT Publishing House, 2025)
The article discusses the problem of defining non-functional requirements when designing CRM systems. The study highlights a tendency in traditional information system development to focus primarily on functional requirements, with non-functional characteristics often being insufficiently formalized.This leads to problems with stability, security, scalability, and user satisfaction. The paper identifies and describes in detail the main groups of non-functional requirements: performance, security, scalability, usability, reliability, and portability. For each group, specific metrics and examples of formalization of requirements are given, such as a 99 % system availability guarantee, a response time of no more than two seconds, a recovery time of no more than 15 minutes, and a recommendation for a three-step process for basic operations. The conclusion of the work is that the correct definition and implementation of non-functional requirements at the CRM system design stage ensures its longevity, security, reliability, and efficiency, contributing to improved customer service quality and enterprise competitiveness. Стаття присвячена проблемі визначення нефункціональних вимог при проектуванні CRM-систем. Дослідження вказує на тенденцію в традиційній розробці інформаційних систем зосереджуватися переважно на функціональних вимогах, тоді як нефункціональні характеристики часто залишаються недостатньо формалізованими. Це призводить до проблем зі стабільністю, безпекою, масштабованістю та задоволеністю користувачів. У роботі визначаються та детально описуються основні групи нефункціональних вимог: продуктивність, безпека, масштабованість, зручність використання, надійність та портативність. Для кожної групи наводяться конкретні метрики та приклади формалізації вимог, такі як гарантія 99% доступності системи, час відповіді не більше двох секунд, час відновлення не більше 15 хвилин, а також рекомендація щодо триетапного процесу для базових операцій. Висновок роботи полягає в тому, що правильне визначення та впровадження нефункціональних вимог на етапі проектування CRM-системи забезпечує її довговічність, безпеку, надійність та ефективність, сприяючи підвищенню якості обслуговування клієнтів і конкурентоспроможності підприємства.
Визначення нефункціональних вимог для CRM-системи
Keywords: Non-functional requirements; CRM system; system portability; system design; нефункціональні вимоги; продуктивність системи; надійність системи; портативність системи